Modelling and analyzing of an active magnetic bearing - Suhail Hadri, Shamsudin (2013)
This project presents a model of an active magnetic bearing which is design and analyzed using COMSOL Multiphysics and also analysis of an active magnetic bearing control system by using MatLab SimuLink. Magnetic flux from an active magnetic bearing is produced when a current is flowing in winding of the ferromagnetic core. To calculate this magnetic flux, the COMSOL Multiphysic is able to automatically calculate with just inserting the input of parameters. From this calculation, simulation of 2D magnetic flux density can be produce by following the step from COMSOL software guide. For control system of an active magnetic bearing, the Newton’s law and the Kirchhoff’s law are applied in order to obtain the right transfer function for the project. Graph resulting PID control for controlling the force, current and position is being plotted by comparing linear system and also non-linear system.